The Ethnographic Narration of Gadulia Lohar Tribe of Udaipur, Rajasthan: With the Special Reference to the Ethnoarchaeological Perspective and Traditional Iron Tool Technology. (27th January 2015) - Tehrani, Neda Hossein
The Gadulias are known by different names in regions, like: Gadulia Lohar in Rajasthan, Madhya Pradesh and Delhi, Gaddi Lohar in Maharashtra, Bhuvariya in Uttar Pradesh and Bhubalia Lohar in Haryana. In Rajasthan the Gadulia Lohar are locally called as Dhurkutia . They claim Rajput origin and Chittorgarh as their ancestral home. This article is a documentation of the Gadulia Lohar's lifestyle, their iron-tool making technology and dress and ornamentation. Ethnographic data grouped with archaeological evidence from Iron Age of this region has also been dealt to understand the mobility pattern of this particular tribe.